Respecting Donors to Biobank Research - Tomlinson, Tom (The Hastings Center report, 2013)
The research importance of biobanked biological materials and their derived data is growing, especially as these are increasingly linked with individual and population-level medical and health information. The number, diversity, and size of biobanks are growing in tandem. So, too, is the number of individuals whose donations are being used in biobank-supported research, with or without their knowledge. Pretty soon, we all will be “participants” in a variety of research projects we know nothing about. Until recently, our leftover tissue or deidentified medical information could be used for research without our consent or even our knowledge. Even if we've been asked–as the current regulations require when research uses are anticipated-we were most likely asked to give a blanket consent to any future use, with no prospect of learning about or controlling how our material is later used. This is an ethically problematic state of affairs, but there are options for improving it.